Molecular cloning and expression study of growth-factor receptor bound protein 7 (grb7) gene in zebrafish development - Tan, Shing Cheng (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Grb7 is a multi-domain adaptor protein which has been postulated to play a role in the regulation of cell migration. The ability to regulate cell migration implies that the protein may be an important component in the progression of cancer as well as in the embryonic development of an organism. Therefore, this study aims to investigate expression pattern of Grb7 throughout the development of zebrafish, whose cell migration process during embryonic development is well-understood. Semi-quantitative RT-PCR was employed to examine the pattern of Grb7 expression in twelve stages of zebrafish development. The results showed that the gene was expressed in all of the stages studied, although the levels of expression differed among the stages. Comparisons with previous studies revealed that the temporal expression pattern of Grb7 corresponded to that of some of its known binding partners, including PDGFR, EGFR and IR. This suggests the possible occurrence of interactions between Grb7 and these molecules during the process of development in zebrafish